A numerical computation and experimental study of air drawing model of polymers in spunbonding nonwoven process. Issue 2 (18th August 2012) - Bo, Zhao
Abstract The air drawing model of polyethylene terephthalate polymer and the model of the air jet flow field in spunbonding process are established. The air jet flow field model is simulated with the help of the finite difference method. The numerical simulation computation results of distributions of the air velocity and air temperature are in agreement with the experimental data. The air drawing model of polymer is solved with the aid of the distributions of the air velocity measured by a particle image velocimetry. The predicted fiber diameters tally with the experimental data well. It can be concluded that the higher initial air temperature can generate finer filament fiber diameter, and the higher initial air velocity can yield the finer fiber diameter as well. The experimental results show that the agreement between the predicted results and the experimental data is very good, which confirms the reliability and the accuracy of these mathematical models. Also, they reveal great prospects for this work in the field of computer assisted design of spunbonding process. POLYM. ENG. SCI., 2013. ©2012 Society of Plastics Engineers